التقليد و التجديد في التدوين التاريخي بين القرنين 5ه-9ه / 11م - 15 م - سارة معيوفي; د/ نور الدين مسعودي (جامعة عمار ثليجي الاغواط, 2024)
الملخص: تتمحور الدراسة حول تتبع نشاط المؤرخين المسلمين في التدوين التاريخي -وما أكثرهم في ذلك الحين - ومدى عكوفهم على فروع التاريخ المختلفة التي أخذوا في تدوينها وترتيبها وترقيتها، وذلك بين القرنين الخامس والتاسع الهجريين في كل من بلاد مصر والشام اللذان كان أبرز البلدان الاسلامية نشاطا في جانب الحركة العلمية والتأليف عموما، خاصة وما طرأ على الكتابة التاريخية من تغيرات سواء على مستوى المنهج أو الموضوع، وكذالك الوقوف على أسباب ودوافع اقتفاء هؤلاء المؤرخين لخطى ومنهج سابقيهم Abstract: This study focuses on the activities of Muslim historians in the field of historical writing, particularly their efforts in documenting, organizing, and advancing various branches of history. The study examines this phenomenon between the 5th and 9th centuries CE in Egypt and the Levant, two of the most prominent Islamic regions in terms of scientific and literary activity. The study investigates the changes that occurred in historical writing during this period, both in terms of methodology and subject matter. It also explores the reasons and motives behind the adherence of these historians to the footsteps and methodology of their predecessors. Additionally, the study sheds light on the new and innovative developments in historical writing and its methodologies, highlighting the most important models of historical writing during this period and identifying its most prominent figures. Keywords :Historicalwriting - Tradition - Innovation من المؤرخين، كما أنها تكشف عن الجديد والتجديد الذي حدث في التدوين التاريخي ومناهجه مع إبراز أهم النماذج المدونة خلال هذه الفترة ومعرفة أشهر أعلامها. الكلمات المفتاحية: التدوين التاريخي - التقليد – التجديد